"'Abbas Mirza's Invitation to Europeans to Settle in Nineteenth-Century Iranian Azerbaijan: Reasons, Causes and Motives". Issue 1 (2nd January 2022) - Shahvar, Soli
ABSTRACT: On July 11, 1823, The Times of London published an open letter by 'Abbas Mirza Qajar, the crown prince of Iran and prince regent of Iranian Azerbaijan, inviting Europeans to come and settle in his province, promising them a range of attractive privileges. The aim of this article is to shed an additional light, through this letter, on the efforts of 'Abbas Mirza in dealing with two key issues, which concerned Iran, in general, and him, in particular. One key issue was domestic, concerning his position as regent, and his desire to strengthen that position, especially vis-a-vis his rivals. The other key issue was external, concerning his efforts to check further Russian advances into southern Caucasus and towards Iran. The article aims to analyze the reasons, motives and timing for the letter, claiming that beyond the declared reason of modernizing his country, 'Abbas Mirza had some undeclared personal and strategic motives behind the writing and the publication of this letter. As the letter was specifically addressed to the British, the analysis will also discuss the reasons behind 'Abbas Mirza's special relations with the British.